Development of Problem-Solving Abilities in Science by Inquiry-Based Learning With Cooperative Learning for Grade 4 Students - Nudjaree Sukontawaree; Apantee Poonputta; Orrasa Prasitnok (Journal of Educational Issues, 2024)
Considering problem-solving ability as an important qualification in the 21st century that could be developed by instructional methods that allow learners to construct their knowledge via questioning through cooperative learning activities, we conducted action research with the purpose of investigating the effectiveness of inquiry-based and cooperative learning on grade 10 students’ problem-solving ability and studying students’ satisfaction with inquiry-based and cooperative learning in developing their problem-solving ability. The participants were 7 grade 4 students in the Thai educational context. They were selected from a class of 20 students using the results of a placement test. The instruments were a learning management plan designed using the integration of inquiry-based learning and cooperative learning, a problem-solving ability evaluation form, and a satisfaction questionnaire. The data was analyzed using the statistics of percentage, mean score, and standard deviation. The result shows that the integration of the two methods was beneficial in improving the problem-solving skills of the majority of the participants. Participants were also satisfied with learning management throughout the semester it was implemented.